Programmable hierarchical plasmonic–photonic arrays via laser-induced film dewetting - Zheng Zeyu; Miao Yu; Yao Jiyuan; Chen Jiamei; Wen Jialin; Chen Xiaodan; Lu Yanxin; Jiang Xiaofang; Shui Lingling (Nanophotonics, 2022)
Hierarchical and periodic nanostructures of dielectrics or metals are highly demanded for wide applications in optical, electrical, biological, and quantum devices. In this work, programmable plasmonic–photonic hierarchical nanostructures are fabricated using a facile and effective method with high controllability and stable reproducibility. The fabrication involves colloidal self-assembly, metal film deposition, and pulsed laser-induced dewetting in sequence for controllably pairing metal nanostructures on dielectric nanospheres in either large area or a local precision. Au nanostructures including Au nanocrown (AuNC), large Au nanosphere (AuNS), and multiple small Au nanoparticles (AuNPs) have been paired one-on-one on assembled SiO2 nanosphere (SiO2NS) arrays, with size and shape controlled by correlating the laser fluence and irradiation time, and the Au film thickness. The fabricated hierarchical nanostructures demonstrate synergistic effect of the photonic effects from the monolayer SiO2NS arrays and the surface plasma resonance effect from the Au nanostructures. The dewetting induced metal film reshaping has been modeled theoretically corresponding to observed experimental results. We can directly “write” the plasmonic Au nanostructures on the photonic crystal array using a focused laser beam to form encode patterns, showing angle-dependent structural colors for anti-counterfeiting information storage and display in rigid/flexible and opaque/transparent devices. It provides a promising path to actively construct on-demand pixelated plasmonic–photonic arrays for optical multiplexing technology in sensing, information encryption, and display.